Classifying finite dimensional cubulations of tubular groups - Woodhouse, DJ (Department of Mathematics at the University of Michigan, 2016)
A tubular group is a group that acts on a tree with Z^2 vertex stabilizers and Z edge stabilizers. This paper develops further a criterion of Wise and determines when a tubular group acts freely on a finite dimensional CAT(0) cube complex. As a consequence we offer a unified explanation of the failure of separability by revisiting the non-separable 3-manifold group of Burns, Karrass and Solitar and relating it to the work of Rubinstein and Wang. We also prove that if an immersed wall yields an infinite dimensional cubulation then the corresponding subgroup is quadratically distorted.